PSYCHOEMOTIONAL STATE OF WOMEN-INTERNALLY DISPLACED PERSONS WITH A THREATENED MISCARRIAGE, LIVING IN THE LUHANSK REGION - Romanenko, I.Yu. (World of Medicine and Biology, 2019)
Prolonged armed conflicts create political, legal, socio-economic problems, form migration flows of the population, affect the somatic and mental health of people. Apart from the fact that women involved in armed conflict are often under the influence of traumatic events and daily stresses at the risk of an increased level of mental illness, pregnancy itself is a critical stage in the development of a woman’s personality. Chronic stress can affect the course of pregnancy, resulting in an increase in the number of complications. Pregnancy is a condition of increased vulnerability to the development of anxiety and depression, which is the most common mental disorder during pregnancy and after childbirth. Their symptoms can range from mild to severe and are a serious public health problem worldwide. According to recent studies, about 54% of women during pregnancy experience anxiety, 34% - depression. The aim of the study was to identify the prevalence and severity of anxiety, depression in pregnant women with threatened miscarriage in the first and second trimesters living in the Luhansk region and having the IDP status to improve treatment and preventive measures and prevent obstetric and perinatal complications in such women. Material and research methods. The study included 220 pregnant women in first and second trimesters of pregnancy who were hospitalized regarding threatened miscarriage in the hospitals, located in the Luhansk region. 48 women of which had IDP status (group I), 172 women without IDP status formed group II. The control group III consisted of 64 pregnant women with clear obstetric anamnesis and physiological course of pregnancy a similar gestational period of pregnancy. Spielberger State-Trait Anxiety Inventory was used to assess the level of anxiety, Beck’s depression Inventory – to asses the level of depression. To describe the serial data, the Me (Q1-Q3) format was used, where Me is the median, Q1 is the 25th quartile, Q3 is the 75th quartile. Valuable differences were evaluated using non-parametric Mann-Whitney test for independent samples. Results and discussion. The average age of women in group I was Me (Q1-Q3) = 26 (23-30.5), group II - 26 (22-33), group III - 27.5 (24-32) years. The largest number of patients was observed at the age of 20-30 years (30 (62.5%), 92 (53.5) and 44 (68.8%) persons, respectively), i.e among the active and able-bodied part of the population. Pregnancy was the first in 26 (54.2%), 112 (65.1%) and 34 (53.1%) women respectively. Patients in groups I and II, compared with women in group III, had significantly higher state anxiety (SA) rates (50.00 (33.50-54.75), 41.00 (30.00-45.50) and 27.00 (24.00 -30.00) respectively), trait anxiety (48.00 (36.00-55.55), 44.00 (30.00-44.00) and 29.00 (26.00-30.00) respectively) and depression (9.00 (5.25-11.00), 8.00 (5.00-10.00) and 6.00 (4.00-7.75) respectively). In pregnant women, Group I, compared with women in group II, showed an excess of SA (P = 0.022) and depression (P = 0.049). The prevalence of elevated SA levels among pregnant women in group I was 83.3%, group II - 68.6%, group III - 9.4%. The prevalence of depression was predominantly mild to 41.7%, 33.1%, and 1.6% respectively. Conclusions. The prevalence of anxiety disorders among pregnant women with threatened miscarriage who have IDP status was in 8.7, depression is 26.1 times more often than in healthy pregnant women that made 83.3% and 41.7% respectively. Indicators of state anxiety and depression in them significantly exceed the same data for women with threatened miscarriage and healthy pregnant women. Antenatal study of levels of anxiety and depression in pregnant women with threatened miscarriage and with IDP status allowed to individualize the approach to the management of pregnancy and if needed to timely develop rehabilitating activities, that will contribute to a successful outcome of the pregnancy and affect the health of the mother and her offspring.